Lithium borohydride-ammonium halide composite solid-state electrolyte, and preparation method and application thereof

The lithium borohydride-ammonium halide composite solid electrolyte, prepared by ammonium halide modifier and specific heat treatment process, solves the problem of low ionic conductivity of lithium borohydride-based electrolytes, achieving high efficiency, stable electrolyte performance and low-cost preparation, which facilitates the application of all-solid-state batteries.

CN122177957AActive Publication Date: 2026-06-09NANJING UNIV OF AERONAUTICS & ASTRONAUTICS
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202610644846.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-05-12
Publication Date
2026-06-09
Estimated Expiration
2046-05-12

Smart Images

  • Figure CN122177957A_ABST
    Figure CN122177957A_ABST
Patent Text Reader

Abstract

The application discloses a lithium borohydride-ammonium halide composite solid electrolyte and a preparation method and application thereof, and belongs to the technical field of solid-state battery electrolyte preparation. The application comprises the following steps: mixing lithium borohydride and ammonium halide to obtain a mixture; under a protective atmosphere, the mixture is heated to 90-180 DEG C and is subjected to heat preservation treatment; and under vacuum conditions, the heat preservation treated material is subjected to heat treatment, thereby obtaining the lithium borohydride-ammonium halide composite solid electrolyte. The application induces lithium borohydride crystal phase transition through ammonium halide decomposition, and effectively removes gaseous by-products through vacuum heat treatment, thereby significantly improving the ionic conductivity and electrochemical stability of the electrolyte, and the preparation process is simple and suitable for large-scale production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of all-solid-state battery electrolyte preparation technology, specifically relating to a lithium borohydride-ammonium halide composite solid electrolyte, its preparation method, and its application. Background Technology

[0002] With socio-economic development and continuously increasing energy demand, lithium-ion battery technology, which combines high energy density, has attracted widespread attention. Replacing traditional graphite anodes with lithium metal anodes is considered an effective way to achieve high-energy-density battery systems, thanks to the extremely high theoretical specific capacity of lithium metal (3860 mAh g⁻¹). -1 The lithium metal anode in liquid batteries exhibits advantages such as high efficiency and low electrode potential. However, in liquid batteries, the lithium metal anode is prone to side reactions with organic electrolytes, leading to decreased coulombic efficiency, deterioration in cycle performance, and safety hazards related to lithium dendrite growth and electrolyte flammability. Therefore, research on non-flammable, thermally stable, and highly ionicly conductive solid-state electrolyte systems has become an important direction for development in this field.

[0003] Solid-state electrolytes, with their core advantages such as high safety, excellent thermal stability, and wide electrochemical window, have become one of the key materials for constructing high-energy-density all-solid-state batteries. They are not only compatible with high-voltage cathodes and lithium metal anodes, but also operate stably over a wide temperature range (-50℃ to 200℃), demonstrating excellent application potential. Among numerous candidate materials, lithium borohydride (LiBH4) has attracted widespread attention due to its advantages of light weight, lithium stability, and high mechanical strength. However, LiBH4 only exhibits ideal ion conductivity in the high-temperature phase, with a room-temperature conductivity of only about 10. -8 S·cm -1 However, its performance falls far short of practical application requirements, significantly limiting its adoption in all-solid-state batteries. Furthermore, LiBH4 faces challenges in practical use, including excessive lithium dendrite growth and a narrow electrochemical window. Studies show that its high electronic conductivity accelerates interfacial side reactions and electrolyte oxidative decomposition, thereby exacerbating dendrite formation and propagation. Simultaneously, dendrites tend to grow along grain boundaries and structural defect regions, further hindering uniform lithium-ion transport and affecting overall battery performance, thus limiting the practical application of LiBH4 as a solid-state electrolyte.

[0004] To address the aforementioned issues, Chinese patent CN109244535A discloses a method for preparing a lithium borohydride-based solid electrolyte. This method involves mixing halogen-doped lithium borohydride with a mesoporous material in a specific ratio, followed by heating and melting impregnation under a high-pressure hydrogen atmosphere. After cooling, a nano-confined halogen-doped lithium borohydride-based solid electrolyte is obtained. The resulting solid electrolyte exhibits good electrochemical stability, but its ionic conductivity needs improvement, and the preparation process carries certain risks. Chinese patent CN119297384A discloses a modified lithium borohydride solid electrolyte and its preparation method. This method involves mixing LiBH4 and lithium halide (LiX) in a specific ratio, followed by high-energy ball milling and heating at 110-150°C under an inert gas atmosphere to obtain an xLiBH4-LiX solid solution. The solid solution is then mixed with B2O3 and subjected to high-energy ball milling to obtain a (xLiBH4-LiX)y-B2O3 solid electrolyte. However, this method involves extremely demanding preparation conditions, including high energy consumption in the two-step high-energy ball milling process and a ball-to-material ratio as high as 70-140:1. Specific values ​​for the electrochemical window are not provided, long-term cycling stability has only been verified for 100 cycles, and compatibility with high-voltage cathode materials has not been fully demonstrated. Therefore, developing LiBH4-based solid electrolytes with high ionic conductivity remains a pressing technical problem in this field. Currently, modified lithium borohydride-based solid electrolytes are still far from meeting the requirements for commercial application in terms of electrochemical performance. Therefore, developing simple and efficient modification strategies to systematically improve their performance in key indicators such as oxidation stability, room-temperature ionic conductivity, and electronic conductivity has become a core issue that urgently needs to be addressed to promote the practical application of this type of electrolyte. Summary of the Invention

[0005] This invention provides a lithium borohydride-ammonium halide composite solid electrolyte, its preparation method, and its application. Using low-cost ammonium halide as raw material, a unique two-step heat treatment process of "first inert gas then vacuum" is adopted. By utilizing the regulatory effect of different atmospheres on the chemical reaction, the effective evolution from raw material to high-performance electrolyte is achieved. The prepared electrolyte has excellent ionic conductivity, electrochemical stability, and electrode compatibility.

[0006] To achieve the above objectives, the present invention adopts the following technical solution: A method for preparing a lithium borohydride-ammonium halide composite solid electrolyte includes the following steps: Lithium borohydride and ammonium halide are mixed to obtain a mixture. Under a protective atmosphere, the mixture is heated to 90°C~180°C and held for heat treatment; The material that has been heat-insulated under vacuum conditions is further heat-treated to obtain a lithium borohydride-ammonium halide composite solid electrolyte.

[0007] In the steps described above, the molar ratio of lithium borohydride to ammonium halide is 20:1 to 1:1; the ammonium halide is one or more of NH4F, NH4Cl, NH4Br and NH4I.

[0008] After mixing lithium borohydride and ammonium halide, the mixture is ground in a mortar and pestle under a protective atmosphere until it is homogeneous. The mortar and pestle grinding is a uniform, intermittent grinding in the same direction for 5 minutes to 1 hour.

[0009] The protective atmosphere is one or more of argon, helium, or nitrogen, and the water content and oxygen content in the protective atmosphere are both less than 0.01 ppm.

[0010] The heating rate to 90℃~180℃ is 1~5℃ / min, and the holding time is 0.5~6 hours. When the temperature is below 90℃, the electrolyte ionic conductivity is low; when the temperature is in the range of 90~180℃, the ionic conductivity increases significantly; further increasing the temperature above 180℃ easily leads to the decomposition of LiBH4, resulting in a decrease in ionic conductivity and poorer stability; therefore, the preferred reaction temperature of this invention is 90~180℃.

[0011] The heat treatment time under vacuum conditions is 5 minutes to 1 hour. If heat treatment is continued under vacuum conditions, an appropriate vacuum heat treatment time should be selected. If the time is too short, the reaction byproducts cannot be completely removed, and the residue of the byproducts will cause a serious decrease in ionic conductivity. If the time is too long, the raw materials will be lost, which will also cause a serious decrease in ionic conductivity.

[0012] The present invention also provides a lithium borohydride-ammonium halide composite solid electrolyte, which is prepared by the above preparation method.

[0013] The aforementioned composite solid electrolyte, prepared using a specific process, achieved an optimized crystal structure and pure interfacial components, exhibiting excellent ion transport performance and electrochemical stability.

[0014] The electrolytes mentioned above can be used in all-solid-state batteries.

[0015] Preferably, the positive electrode material of the all-solid-state battery includes at least one of nickel-cobalt-manganese ternary positive electrode material, transition metal sulfide-based positive electrode material, sulfur-based positive electrode material, and selenium-based positive electrode material; the negative electrode material of the all-solid-state battery includes at least one of carbon-based negative electrode material, transition metal oxide-based negative electrode material, lithium metal negative electrode material, silicon-based negative electrode material, and tin-based negative electrode material.

[0016] Beneficial Effects: This invention provides a lithium borohydride-ammonium halide composite solid electrolyte, its preparation method, and its application. Using ammonium halide as a modifier, a two-step heat treatment process involving inert gas and vacuum is employed to achieve highly efficient modification of the lithium borohydride-based electrolyte. Compared with existing technologies, this invention offers the following advantages: 1. This invention effectively solves the core technical problem of low ionic conductivity in traditional lithium borohydride solid electrolytes. By combining ammonium halide with lithium borohydride, the ionic conductivity of the composite solid electrolyte is significantly improved. The core role of ammonium halide in this invention is to undergo an in-situ chemical reaction with lithium borohydride. When preparing a solid electrolyte by combining lithium borohydride with ammonium halide (NH4X), two main types of products are generated that are beneficial to improving ionic conductivity: one is the lithium borohydride ammoniated complex Li(NH3) induced by NH3 released in situ from ammonium halide. n BH4; secondly, some BH4 - Ligands are halogenated X - The substitution to form Li4(BH4)3X, together with the lithium borohydride electrolyte, results in high ionic conductivity at lower temperatures. This improves the uniformity of lithium-ion supply during charge and discharge, suppresses interfacial charge accumulation and overpotential rise, thereby reducing lithium dendrite formation and side reactions. Simultaneously, the high conductivity reduces battery internal resistance, slows capacity decay, and enables the full cell to achieve high capacity retention and stable coulombic efficiency, ultimately achieving stable long-cycle operation. The above process increases the ionic conductivity of the composite electrolyte by more than four orders of magnitude compared to pure LiBH4. The lithium borohydride-based electrolyte prepared in this invention achieves an ionic conductivity of up to 10 at 50°C. -3 S cm -1 .

[0017] 2. This invention uses low-cost ammonium halide as a raw material, which significantly reduces the preparation cost of the composite solid electrolyte compared to existing preparation methods that use high-cost lithium halide. Furthermore, this invention achieves good economic efficiency without sacrificing the overall electrochemical performance of the electrolyte, thereby enhancing its market competitiveness.

[0018] 3. This invention employs a two-step heat treatment process of "inert gas first, then vacuum," fully leveraging the regulatory effects of different atmospheres on the chemical reaction to achieve efficient and stable conversion of raw materials into high-performance composite electrolytes. The vacuum environment effectively removes excess byproducts generated during the reaction, suppresses the formation of low-conductivity phases, ensures the stability and consistency of electrolyte performance, and further enhances the overall electrochemical performance of the composite electrolyte.

[0019] 4. The preparation method of this invention is simple, convenient to operate, and has good repeatability. It does not require complex equipment or harsh preparation conditions, and is easy to scale up. It effectively solves the technical problems of complex preparation processes and difficulty in mass production of existing high-performance solid electrolytes, reduces the production threshold and production cost, facilitates industrial promotion and application, and has good industrial application prospects. Attached Figure Description

[0020] Figure 1The X-ray diffraction (XRD) patterns of the composite electrolytes of lithium borohydride and ammonium halide obtained in Example 1 and Comparative Example 1 of this invention are shown. Figure 2 This is a scanning electron microscope (SEM) image of the composite electrolyte material of lithium borohydride and ammonium halide in Example 1 of the present invention; Figure 3 The graph shows the ionic conductivity of the composite electrolyte materials of lithium borohydride and ammonium halide in Examples 1, 1, and 2 of the invention as a function of temperature under different heat treatment conditions and different halide raw materials. Figure 4 This is a DC polarization curve of the composite electrolyte material of lithium borohydride and ammonium halide in Example 2 of the invention; Figure 5 The critical current density diagram of the composite electrolyte material of lithium borohydride and ammonium halide in Embodiment 2 of the invention; Figure 6 Critical current density diagram of the composite electrolyte material of lithium borohydride and ammonium halide in Comparative Example 3 of the invention; Figure 7 This is a graph showing the ion transference number of the composite electrolyte material of lithium borohydride and ammonium halide in Example 4 of the present invention. Figure 8 This is a schematic diagram showing the electrochemical stability test results of the composite electrolyte material of lithium borohydride and ammonium halide in Example 3 of the present invention; Figure 9 This is a test diagram of the long-cycle performance of a lithium symmetric battery assembled with a composite electrolyte material of lithium borohydride and ammonium halide in Example 4 of the present invention. Figure 10 The charge-discharge curves and coulombic efficiency diagrams of the lithium-sulfur all-solid-state battery assembled with the composite electrolyte material of lithium borohydride and ammonium halide in Example 5 of this invention are shown at 0.1C. Detailed Implementation

[0021] The present invention will now be described in detail with reference to the accompanying drawings and specific embodiments: Example 1

[0022] A preparation process for a lithium borohydride-ammonium halide composite solid electrolyte includes the following steps: Under non-oxidizing gas conditions (H2O < 0.01 ppm, O2 < 0.01 ppm), LiBH4:NH4F:NH4Cl are weighed in a molar ratio of 7:2:1 and added to a mortar, with a total mass of 1g. The mixture is manually ground intermittently for 10 minutes, with a 2-minute break after every 5 minutes of grinding. After being manually ground and mixed evenly, the mixture is transferred to a stainless steel mold, pressed into tablets under a non-oxidizing gas atmosphere, and then transferred to a heating container. The tablets are heated to 120°C at a heating rate of 2°C / min and held at that temperature for 2 hours. Then, the tablets are vacuum heat-treated for 5 minutes and allowed to cool naturally to room temperature. The cooled material is then removed from the sealed container and manually ground into powder using a mortar. The resulting product is a lithium borohydride-fluorine / ammonium chloride composite electrolyte.

[0023] Example 2

[0024] The preparation process of a lithium borohydride-ammonium halide composite solid electrolyte is basically the same as that in Example 1, except that NH4Cl is replaced with NH4Br, the molar ratio of LiBH4:NH4F:NH4Br is 6:2:2, the heat treatment time is 6h, the vacuum heat treatment time is 25min, and then it is naturally cooled to room temperature. The product obtained is a lithium borohydride-fluorine / ammonium bromide composite electrolyte.

[0025] Example 3

[0026] The preparation process of a lithium borohydride-ammonium halide composite solid electrolyte is basically the same as that in Example 1, except that NH4Cl is replaced with NH4I, the molar ratio of LiBH4:NH4F:NH4I is 5:3:2, the heat treatment temperature is 90℃, the vacuum heat treatment time is 1 hour, and the product obtained is lithium borohydride-fluorine / ammonium iodide composite electrolyte.

[0027] Example 4

[0028] The preparation process of a lithium borohydride-ammonium halide composite solid electrolyte is basically the same as that in Example 1, except that NH4F is replaced with NH4Br, the molar ratio of LiBH4:NH4Cl:NH4Br is 7:1:2, the heat treatment temperature is 160℃, the time is 3 hours, the vacuum heat treatment time is 15 minutes, and the product obtained is lithium borohydride-chlorine / ammonium bromide composite electrolyte.

[0029] Example 5

[0030] The preparation process of a lithium borohydride-ammonium halide composite solid electrolyte is basically the same as that in Example 1, except that NH4F is replaced with NH4I, the molar ratio of LiBH4:NH4Cl:NH4I is 6:2:2, the heat treatment temperature is 140℃, the vacuum heat treatment time is 35 minutes, and the product obtained is lithium borohydride-chloride / ammonium iodide composite electrolyte.

[0031] Example 6

[0032] The preparation process of a lithium borohydride-ammonium halide composite solid electrolyte is basically the same as that in Example 1, except that NH4F and NH4Cl are replaced with NH4Br, the molar ratio of LiBH4:NH4Br is 5:5, the heat treatment temperature is 100℃, the heat treatment time is 4 hours, and the product obtained is lithium borohydride-ammonium bromide composite electrolyte.

[0033] Example 7

[0034] The preparation process of a lithium borohydride-ammonium halide composite solid electrolyte is basically the same as that in Example 1, except that NH4F and NH4Cl are replaced with NH4Br and NH4I, the molar ratio of LiBH4:NH4Br:NH4I is 9:0.5:0.5, the heat treatment temperature is 180℃, the heat treatment time is 2.5 hours, the vacuum heat treatment time is 20 minutes, and the obtained product is lithium borohydride-bromine / ammonium iodide composite electrolyte.

[0035] Comparative Example 1 Preparation of lithium borohydride-ammonium halide composite solid electrolyte in one-step heat treatment: Process differences: LiBH4:NH4F:NH4Cl were weighed in a molar ratio of 7:2:1 and added to a mortar, with a total mass of 1g. After being kept at 120℃ for 2 hours, no vacuum heat treatment was performed. The remaining steps were the same as in Example 1.

[0036] Testing revealed that the voltage window of the lithium borohydride-based solid electrolyte prepared in this comparative example was only 2.8V, indicating that the electrolyte lacks high-voltage stability. The measured critical current density of this electrolyte was only 1.9 mA cm⁻¹. -2 Its ionic conductivity at 50℃ is 2.01×10⁻⁶. -6 S cm -1 ( Figure 3 The dendrite suppression ability of the composite electrolytes prepared in Examples 1-7 is significantly different.

[0037] Comparative Example 2 Lithium borohydride-lithium chloride composite solid electrolyte: Process differences: LiBH4 and LiCl were mixed in a molar ratio of 7:3 (keeping the total molar amount of halides constant). The mixture was heated to 120°C at a heating rate of 2°C / min, held at that temperature for 2 hours, and then subjected to vacuum heat treatment for 5 minutes. The remaining steps were the same as in Example 1.

[0038] Testing revealed that the voltage window of the lithium borohydride-based solid electrolyte prepared in this comparative example was only 3.0 V, indicating that the electrolyte lacks high-voltage stability. The measured critical current density of this electrolyte was only 2.0 mA cm⁻¹. -2 Its ionic conductivity at 50℃ is 5.11 × 10⁻⁶. -5 S cm -1 ( Figure 3 The dendrite suppression performance of the composite electrolytes prepared in Examples 1-7 differs significantly from that of the composite electrolytes prepared in Examples 1-7.

[0039] Comparative Example 3 Two-step high-temperature heat treatment for the preparation of lithium borohydride-ammonium halide composite solid electrolyte: Process differences: LiBH4:NH4F:NH4Cl were weighed in a molar ratio of 7:2:1 and added to a mortar, with a total mass of 1g. The mixture was kept at 200℃ for 2 h and then vacuum heat-treated for 5 min. The remaining steps were the same as in Example 1.

[0040] Results and disadvantages: Testing showed that the critical current density of the lithium borohydride-based solid electrolyte prepared in this comparative example was only 1.6 mA cm⁻¹. -2 ( Figure 6 The ionic conductivity at 50℃ is 2.01 × 10⁻⁶. -7 S cm -1 The dendrite suppression performance of the electrolyte differs significantly from that in Examples 1-7.

[0041] like Figure 1 To determine the phase composition of the lithium borohydride-ammonium halide composite electrolytes obtained in Example 1 and Comparative Example 1, X-ray diffraction (XRD) was used. The materials were tested within the 10-60° range at a scan rate of 5° / min. The X-ray source used a copper target, a tube voltage of 40 kV, and a tube current of 40 mA. The obtained XRD patterns are shown below. Figure 1 As shown, in the lithium borohydride-ammonium halide composite electrolyte, lithium borohydride has been transformed into a hexagonal phase with higher conductivity, while the overall electrolyte material still exists stably as hexagonal lithium borohydride.

[0042] like Figure 2 The scanning electron microscope (SEM) image of the composite electrolyte obtained in Example 1 shows that the electrolyte sample is in the form of micron-sized particles with uniform size and shape, thus having a uniform electrochemical reaction interface.

[0043] like Figure 3 The graph shows the ionic conductivity of the composite electrolyte materials prepared from lithium borohydride and ammonium halide in Examples 1, 1, and 2 under different heat treatment conditions and with different halide raw materials, as a function of temperature. It can be seen from the graph that the two-step heat treatment method can further improve the ionic conductivity, reaching 1.58 × 10⁻⁶ at 30°C. -4 S cm -1 Its ionic conductivity reaches 10 at 50℃. -3 S cm -1 The introduction of ammonium halide increased the ionic conductivity of lithium borohydride, indicating that it can efficiently modulate the conductivity of Li. + Migration in solid electrolytes helps improve Li + Deposition kinetics to improve the electrochemical performance of lithium metal batteries.

[0044] like Figure 4 For the self-discharge rate and long-term reliability test of the battery assembled with the composite electrolyte obtained in Example 2, the suppression of electron migration can block the reduction of lithium ions inside the electrolyte, thereby reducing the risk of short circuit caused by lithium dendrites penetrating the separator.

[0045] like Figure 5 To test the critical current density of the composite electrolyte obtained in Example 2, the reversibility of lithium deposition / stripping behavior of borohydride-ammonium halide was tested at different current densities. The synthesized electrolyte was tested at 0.1-2.8 mA cm⁻¹. -2 The deposition / stripping behavior remains stable at current density, demonstrating that the proposed modification method can effectively suppress lithium dendrite growth and promote uniform lithium deposition, thereby significantly extending the cycle life of the battery and improving its safety and reliability, thus contributing to the cycle stability of the all-solid-state battery.

[0046] like Figure 6 To test the critical current density of the composite electrolyte obtained in Comparative Example 3, it was found that the composite electrolyte's ability to resist dendrite formation decreased significantly after increasing the heat treatment temperature. Excessively high heat treatment temperatures can easily lead to excessive decomposition of raw materials, resulting in decreased ionic conductivity and poorer stability.

[0047] like Figure 7 The ion transference number test of the composite electrolyte obtained in Example 4 shows that it has a high lithium ion transference number. This characteristic effectively suppresses anion polarization during the charging and discharging process, resulting in a very small ion concentration gradient inside the electrolyte, thereby avoiding the loss of active lithium caused by ion transport lag at the interface.

[0048] like Figure 8The linear sweep voltammetry test of the composite electrolyte obtained in Example 3 is used to determine the electrochemical stability window of the solid electrolyte. By applying an increasing voltage at a constant rate and monitoring the abrupt change in current, this method can accurately identify the decomposition voltage onset potential of the electrolyte, thereby defining its safe operating voltage range and ensuring that the all-solid-state battery has good cycle stability and safety when matched with a high-voltage cathode.

[0049] like Figure 9 For the lithium-symmetric battery cycle test of the composite electrolyte obtained in Example 4 of this invention, in order to further evaluate the stability of the electrolyte during long-term cycling, a 0.2 mA cm⁻¹ test was conducted. -2 At the specified current density, continuous lithium deposition / stripping of the electrolyte can be sustained for at least 1000 hours, demonstrating excellent compatibility and stability with the lithium metal anode.

[0050] like Figure 10 To test the cycle performance of the all-solid-state battery assembled with the composite electrolyte obtained in Example 5, this example uses a dedicated solid-state battery test mold to characterize the electrochemical performance of the prepared lithium borohydride-based solid-state electrolyte. All battery assembly processes were completed in a glove box protected by an inert atmosphere. When evaluating the full-cell performance of this electrolyte matched with a lithium metal anode and a sulfide cathode, a constant current charge-discharge method was used to test the battery's electrochemical performance. At 0.1C, the cycle performance curve within a voltage window of 1-2.5 V showed stable cycling for 193 cycles, with a coulombic efficiency of 99.8%.

[0051] In summary, the present invention mainly generates two types of products that are beneficial to improving ionic conductivity during the preparation of solid electrolytes by combining lithium borohydride and ammonium halide (NH4X): one is the lithium borohydride ammoniated complex Li(NH3) induced by NH3 released in situ from ammonium halide. n BH4; secondly, some BH4 - Ligands are halogenated X - The substitution to form Li4(BH4)3X can be achieved by adjusting the NH3 and halogen X. -The combined effect of these factors results in high ionic conductivity of the electrolyte at lower temperatures, improving the uniformity of lithium-ion supply during charging and discharging, suppressing interfacial charge accumulation and overpotential rise, thereby reducing lithium dendrite formation and side reactions. Simultaneously, the high conductivity reduces battery internal resistance, slows capacity decay, and enables the full cell to achieve high capacity retention and stable coulombic efficiency, ultimately achieving long-term stable operation. The prepared lithium borohydride-based solid electrolyte possesses a wide electrochemical window of 0–5.0 V and excellent electrode compatibility. Furthermore, it can achieve reversible lithium metal plating / stripping for over 1000 hours. Full-scale solid-state batteries assembled with it, along with lithium metal anodes and sulfide cathodes, also exhibit stable long-cycle performance, making it a stable solid electrolyte.

[0052] The above description is merely a preferred embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any variations or substitutions that can be easily conceived by those skilled in the art within the technical scope disclosed in the present invention should be included within the scope of protection of the present invention. Therefore, the scope of protection of the present invention should be determined by the scope of the claims.

Claims

1. A method for preparing a lithium borohydride-ammonium halide composite solid electrolyte, characterized in that, include: Lithium borohydride and ammonium halide are mixed to obtain a mixture. Under a protective atmosphere, the mixture is heated to 90°C~180°C and held for heat treatment; The material that has been heat-insulated under vacuum conditions is further heat-treated to obtain the lithium borohydride-ammonium halide composite solid electrolyte.

2. The method for preparing the lithium borohydride-ammonium halide composite solid electrolyte according to claim 1, characterized in that, The molar ratio of lithium borohydride to ammonium halide is 20:1 to 1:

1.

3. The method for preparing the lithium borohydride-ammonium halide composite solid electrolyte according to claim 1 or 2, characterized in that, The ammonium halide includes at least one of ammonium fluoride, ammonium chloride, ammonium bromide, and ammonium iodide.

4. The method for preparing the lithium borohydride-ammonium halide composite solid electrolyte according to claim 1, characterized in that, Under a protective atmosphere, the heating rate to 90℃~180℃ is 1~5℃ / min, and the holding time is 0.5~6 hours.

5. The method for preparing the lithium borohydride-ammonium halide composite solid electrolyte according to claim 1, characterized in that, The heat treatment continues under vacuum conditions for 5 minutes to 1 hour.

6. The method for preparing the lithium borohydride-ammonium halide composite solid electrolyte according to claim 1, characterized in that, The process may include grinding, mixing, and tableting the materials before, during, or after mixing lithium borohydride with ammonium halide.

7. The method for preparing the lithium borohydride-ammonium halide composite solid electrolyte according to claim 1 or 4, characterized in that, The protective atmosphere includes at least one of argon, nitrogen, or helium.

8. The method for preparing the lithium borohydride-ammonium halide composite solid electrolyte according to claim 7, characterized in that, The water and oxygen content in the protective atmosphere are both less than 0.01 ppm.

9. A lithium borohydride-ammonium halide composite solid electrolyte, characterized in that, It is prepared by any one of claims 1 to 8.

10. The application of the lithium borohydride-ammonium halide composite solid electrolyte according to claim 9, characterized in that, The composite solid electrolyte is used in all-solid-state batteries.

Citation Information

Patent Citations

  • Composite hydrogen storage material and preparation method thereof

    CN105947976A

  • Preparation method of lithium borohydride-based solid electrolyte material

    CN109244535A

  • Lithium ion conductor of ammonia-doped lithium borohydride composite material system and preparation method of lithium ion conductor

    CN112331909A

  • Conductive material-doped multi-ion-path solid electrolyte as well as preparation method and application thereof

    CN117996159A

  • Modified lithium borohydride solid electrolyte and preparation method thereof

    CN119297384A